The effectiveness of behavioural cognitive mentoring in reducing psychological stress among mothers of children with cerebral palsy - Khalaf Alsmadi, Mohammad Shaban
Parents respond in many diverse ways to raising a child with special needs, ranging from gaining insights and appreciation for the gifts and personal growth that the child has brought, to feelings of grief over the loss of the expected child. Furthennore, the opposite occurs when the child with special needs impacted the whole family, resulting in the distress of parents from psychological stress that needs professional assistance from specialists and counsellors. Based on this premise, the study aims to detennine the effectiveness of the cognitive behavioural mentoring program in reducing cognitive and psychological problems of the child's independent performance among mothers of children with cerebral palsy in post-evaluation. The research is based on quantitative data involving a quasi-experimental research approach which were collected from 50 mothers of children with special needs from Irbid City, Jordan. The data were analysed' using the Statistical Package for the Social Science (SPSS) ver ion 25 and treated using descriptive and inferential statistics. The statistical tests used in the study were Mann Whitney U and Wilcoxon signed-rank test. The Mann-Whitney U results revealed that the experimental group perfonned significantly better than those in the control group in both three stages of the .distribution of questionnaires, specifically the mothers of children with cerebral palsy. Additionally the Wilcoxon Signed-Rank test showed that there was a significant difference in the experimental group before, after and delayed exposure to the program. Nevertheless, this is not the case for the control group as the results showed insignificant difference before, after and delayed distribution of the questionnaires. The study contributed by designing a l2-session Cognitive Behavioural Mentoring Program for effective intervention for mothers of children with cerebral palsy. It also focuses on the main psychological, behavioural and cognitive domains to reduce the stress among mothers of children with cerebral palsy. Therefore, it is suggested that the government should provide more training sessions, employ the collaborative activity as an out-of-class assignment, and carefully monitor the process as well as providing sufficient services and support for mothers of children with cerebral palsy.